2021
DOI: 10.1037/adb0000732
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy challenge interventions to reduce alcohol consumption among high school and college students: A meta-analysis.

Abstract: Objective: Alcohol expectancies are a critical factor in the development of problematic alcohol use. Expectancy challenge (EC) interventions aim to manipulate positive alcohol expectancies to reduce or prevent alcohol use among young people. The present meta-analysis investigated the effects of ECs at changing expectations and alcohol use among high school and college students, and moderating effects of study and individual characteristics on these changes. Method: A total of 23 EC studies (N = 4,122; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…Similarly, the methods of delivery have to be adjusted to the targeted age group: While administration of alcohol in an experimental bar setting is an appropriate element of expectancy challenging interventions with college students, a non-bar delivery format (e.g. use of videos or other didactic material) would be needed for younger populations who are not in the legal drinking age [40].…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Similarly, the methods of delivery have to be adjusted to the targeted age group: While administration of alcohol in an experimental bar setting is an appropriate element of expectancy challenging interventions with college students, a non-bar delivery format (e.g. use of videos or other didactic material) would be needed for younger populations who are not in the legal drinking age [40].…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Second, psychosocial interventions in pain populations have been effective in promoting use of alternate, more adaptive means of coping with pain (Kashikar-Zuck et al, 2013; Keefe et al, 1990), and these could be tailored to address BZD-related pain coping. Finally, outcome expectancies can be targeted directly to reduce substance use behaviors (Gesualdo & Pinquart, 2021). For example, a manipulation of analgesia expectancies for cigarette smoking was previously shown to decrease urge to smoke and increase latency to cigarette use (Ditre et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. reduce substance use behaviors (Gesualdo & Pinquart, 2021). For example, a manipulation of analgesia expectancies for cigarette smoking was previously shown to decrease urge to smoke and increase latency to cigarette use (Ditre et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that changes in expectations may lead to behavior change. A meta-analysis examining the effects of expectancy challenge (EC) interventions among college students in the United States and Europe showed that a reduction of student's positive alcohol expectations achieved through participation in the EC was related to a significant decrease in positive alcohol expectations (Gesualdo & Pinquart, 2021 ).…”
Section: Influences On Health Behaviorsmentioning
confidence: 99%